2004
DOI: 10.1097/00000542-200402000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of the Inhibitory Effects of Propofol and Thiamylal on Sarcolemmal Adenosine Triphosphate–sensitive Potassium Channels

Abstract: These results suggest that the major effects of both propofol and thiamylal on KATP channel activity are mediated via the Kir6.2 subunit. Site-directed mutagenesis study suggests that propofol and thiamylal may influence Kir6.2 activity by different molecular mechanisms; in thiamylal, the SUR subunit seems to modulate anesthetic sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…For example, differences between the prior porcine study with HMR 1883 [13] and the present study include the duration of coronary occlusion (20 vs 90 min), the use of autonomic blockade in the present study and the type of anaesthesia (pentobarbital versus α-chloralose). Barbiturate anaesthetics may independently block mitochondrial [45] and sarcolemmal [46] K ATP channels. In the prior porcine study [13], it should also be noted that while HMR 1883 reduced ventricular fibrillation during ischaemia, 5 of 12 treated pigs developed ventricular fibrillation during the first few minutes of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, differences between the prior porcine study with HMR 1883 [13] and the present study include the duration of coronary occlusion (20 vs 90 min), the use of autonomic blockade in the present study and the type of anaesthesia (pentobarbital versus α-chloralose). Barbiturate anaesthetics may independently block mitochondrial [45] and sarcolemmal [46] K ATP channels. In the prior porcine study [13], it should also be noted that while HMR 1883 reduced ventricular fibrillation during ischaemia, 5 of 12 treated pigs developed ventricular fibrillation during the first few minutes of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Kalkan et al 24 reported that the activation of K ATP channels seemed to be one of the mechanisms by which propofol induced beneficial effect on contractility of myocardium in hypercholesterolemic rabbit hearts. Kawano et al 25 reported that Values are mean ± SD (n = 6 per group). CoNT = control; P-25 = 25 µM propofol group; P-50 = 50 µM propofol; P-CoNT = control with pacing; P-P25 = 25 µM propofol with pacing; P-P50 = 50 µM propofol with pacing; 5-HD = 5-hydroxydecanoic acid; HMr = HMr1098.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological experiments have shown that isoflurane may activate K ATP channels at a moderately acidic intracellular pH of 6.8 [16] or facilitate the opening of channels via the activation of protein kinase C [17]. In contrast, our previous patch-clamp experiments indicated that high supraclinical concentrations of propofol directly inhibited the cardiac K ATP -channel activity [18,19]. Ketamine also inhibits recombinant cardiac K ATPchannel activity in a concentration-dependent manner [20].…”
Section: Cardiac K Atp Channel (Sarcolemmal Channel)mentioning
confidence: 80%